Stand density management diagrams for two mediterranean pine species in easter spain - Valbuena, P.=700 1 Del Peso, C.; Bravo, F.
(En, Es)
ilus., 25 ref.
Keywords: PINUS HALEPENSIS; PINUS PINASTER; DENSIDAD; SILVICULTURA; ESPAÑA; DIAGRAMA; INVESTIGACION AGRARIA: SISTEMAS Y RECURSOS FORESTALES